Effect of fulvic acid on bioreactor performance and on microbial populations within the anammox process. (December 2020) - Zhang, Li; Wang, Yueping; Soda, Satoshi; He, Xiaosong; Hao, Shiwei; You, Yue; Peng, Yongzhen
Highlights: The anammox performance was promoted at proper fulvic acid (FA) concentration. Changes occur in the microbial community, due to long-term exposure to FA. Candidatus Jettenia and Candidatus Kuenenia can tolerate high content of FA. Sludge granulation is improved during FA exposure. Granular activated carbon can accelerate the start-up of anammox process. Abstract: The long-term effect of fulvic acid (FA) on bioreactor performance and on microbial populations within the anammox process were firstly investigated in this study. The average nitrogen removal rate showed an upward trend when the influent TOC concentration of FA was 25.2–65.1 mg/L. However, when FA was increased to 80.3 mg/L, the reactor performance was slightly inhibited. In addition, judging from the particle size and settling properties, FA can promote anammox sludge granulation. After 53 days of exposure to FA, the genus Anaerolinea increased in number, while Denitratisoma decreased. Candidatus Jettenia and Candidatus Kuenenia survived and enriched in the changed environment, potentially due to the interaction between anammox bacteria and some heterotrophic bacteria, which could protect anammox bacteria from adverse environments. These results indicate that FA can change the bacterial community and trigger different microbial interaction mechanisms within the anammox reactor.